2014
DOI: 10.1111/jipb.12145
|View full text |Cite
|
Sign up to set email alerts
|

Farinose flavonoids are associated with high freezing tolerance in fairy primrose (Primula malacoides) plants

Abstract: The deposition of surface (farinose) flavonoids on aerial parts of some Primula species is a well-documented but poorly understood phenomenon. Here, we show that flavonoid deposition on the leaves and winter buds may contribute strongly to preventing freezing damage in these plants. The ice nucleation temperature of fairy primrose (Primula malacoides) leaves covered with natural flavone was approximately 6 °C lower compared to those that had their flavone artificially removed. Additionally, farinose flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Similar flavonoid excretions were found in other Betulaceae ( Alnus , Betula , Ostrya ) and Salicaceae ( Populus Wollenweber, ), some of them having the most frost hardiest buds ever reported (−253°C Tumanov, Krasvatsev, & Khvalin, ). Only recently, flavonoid deposition on the surface of aerial parts of Primula malacoides was discussed to lower ice nucleation temperature in the leaves and thereby contributing strongly to prevent freezing damage (Isshiki, Galis, & Tanakamaru, ). Flavonoid glycosides (Kasuga et al, ; Kasuga et al, ) and tannin‐related polyphenols (Kuwabara et al, ) have also been reported to play an important role as supercooling‐facilitating (anti‐ice nucleation) active substances in xylem ray parenchyma cells of certain species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar flavonoid excretions were found in other Betulaceae ( Alnus , Betula , Ostrya ) and Salicaceae ( Populus Wollenweber, ), some of them having the most frost hardiest buds ever reported (−253°C Tumanov, Krasvatsev, & Khvalin, ). Only recently, flavonoid deposition on the surface of aerial parts of Primula malacoides was discussed to lower ice nucleation temperature in the leaves and thereby contributing strongly to prevent freezing damage (Isshiki, Galis, & Tanakamaru, ). Flavonoid glycosides (Kasuga et al, ; Kasuga et al, ) and tannin‐related polyphenols (Kuwabara et al, ) have also been reported to play an important role as supercooling‐facilitating (anti‐ice nucleation) active substances in xylem ray parenchyma cells of certain species.…”
Section: Discussionmentioning
confidence: 99%
“…Similar flavonoid excretions were found in other Betulaceae (Alnus, Betula, Ostrya) and Salicaceae (Populus Wollenweber, 1989), some of them having the most frost hardiest buds ever reported (− 253°C Tumanov, Krasvatsev, & Khvalin, 1959). Only recently, flavonoid deposition on the surface of aerial parts of Primula malacoides was discussed to lower ice nucleation temperature in the leaves and thereby contributing strongly to prevent freezing damage (Isshiki, Galis, & Tanakamaru, 2014). Flavonoid glycosides (Kasuga et al, 2010;Kasuga et al, 2013) FIGURE 9 Changes of total actual water potential of bud tissues of Alnus alnobetula: (a) with season (mean values per sampling date) and (b) in response to controlled freezing treatments (starting temperature +5°C, cooling rate 5 K/h, target temperature <−40°C).…”
Section: Freeze Dehydration Of Buds Towards the Stemmentioning
confidence: 99%
“…Similarly, farinose flavonoids are excreted to the surfaces of aerial organs of for example Primula species, where they inhibit ice crystallization and thereby improve tolerance to mild freezing temperatures (Isshiki et al . ). Also, inhibitor studies in pine seedlings suggest a direct role of flavonoids in plant freezing tolerance (Teklemariam & Blake ).…”
Section: Introductionmentioning
confidence: 97%
“…Some flavonoids that are accumulated in the cold are able to depress the freezing point of plant cells or tissues and contribute to the deep supercooling ability of xylem parenchyma cells in katsura trees (Kasuga et al 2008). Similarly, farinose flavonoids are excreted to the surfaces of aerial organs of for example Primula species, where they inhibit ice crystallization and thereby improve tolerance to mild freezing temperatures (Isshiki et al 2014). Also, inhibitor studies in pine seedlings suggest a direct role of flavonoids in plant freezing tolerance (Teklemariam & Blake 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are well known as antioxidant by scavenging reactive oxygen species during stress (Agati et al ). In addition, flavonoids are associated with high freezing tolerance, and exogenous application of flavone could be used to reduce freezing damage (Isshiki et al ). In some ways, the roles that polyphenols play in developmental processes of plants are consistent with those of jasmonates (JAs) and suggested their effect on JA signaling (Wasternack and Hause ).…”
Section: Introductionmentioning
confidence: 99%